Association between dental caries and adherence to the Mediterranean diet, dietary intake, and body mass index in children - Kübra Esin; Beyza Ballı-Akgöl; Saniye Sözlü; Betul Kocaadam-Bozkurt (BMC Oral Health, 2024)
Abstract Background Children with healthier nutritional status are less likely to develop severe caries than those with a high-sugar content diet. Studies evaluating dental caries and nutritional status in school-age children have generally focused on dietary intake, diet quality, or anthropometric measures, and the number of studies evaluating them together is limited. Objective It was aimed to evaluate the relationship between dental caries adherence to the Mediterranean Diet (MD), dietary intake, and Body Mass Index (BMI) in school-age children. Materials and methods This study was conducted with 300 healthy children (52.0% boys, 48.0% girls) aged between 6 and 12 years. The data collection forms included sociodemographic characteristics, oral health practices of children, Mediterranean Diet Quality Index for children and adolescents (KIDMED), and food consumption records. Anthropometric measurements (body weight and height) of the children were taken. Dental examinations were performed by a pediatric dentist. Results While the DMFT mean score of the children was 1.7 ± 2.09, the mean dft score was 2.9 ± 3.29. The mean of KIDMED scores was 5.9 ± 3.32. DMFT and dft scores decreased statistically as maternal education increased (p < 0.05). DMFT and dft scores were not statistically different between BMI groups according to gender and age (p > 0.05). DMFT scores differed statistically between KIDMED groups (p < 0.05). This difference was between low-optimal and low-improvement-needed groups. While there was a low negative correlation (r=-0.169) between calcium intake and DMFT score, a low positive correlation was found between glucose (r = 0.172) and fructose (r = 0.149) intake and dft score (p < 0.05). In regression analysis, while the children’s age related DMFT scores positively, maternal education and KIDMED scores related DMFT scores negatively. Also, children’s age and maternal education related dft scores negatively. Conclusion In this study, adherence to the MD rather than nutrients was found to be important in dental caries. Also maternal education level was also found to be a determinant factor in dental caries in children. DMFT and dft did not differ between BMI groups.Further studies should be conducted to assess the impact of the MD on dental caries in children to develop dietary interventions for preventative purposes.